Inspection confirmed mold damage in schools and new use of drugs for airway obstruction: A cohort study - Juha Pekkanen; Martin Täubel; Lauri Lehtimäki; Tero Marttila; Anne M. Karvonen (PLoS ONE, 2025)
New asthma is considered the most important possible long-term consequence of indoor dampness and mold. However, there are no prospective studies available from schools, there is insufficient evidence on dose-response, and no consensus on how exposure should be assessed. In Finland, visible mold is rare in schools and invasive methods are used to detect mold hidden in building structures. Objective To test if extent and severity of mold damage in school buildings increases the risk of new use of drugs for airway obstruction among students with a dose-response. Methods Extent of mold damage in 110 Finnish primary and secondary school buildings in 2004 was estimated based on all technical inspections done by 2021. New asthma (n = 1,035) and use of drugs for obstructive airway diseases (n = 3,162) among 30,418 students by 2019 was defined based on drug purchases. Multilevel Cox models were adjusted for confounders obtained from Medical Birth Register. Results Extensive mold damage was common. Nine buildings had no or small mold damage, 19 buildings limited, 44 wide and 38 very wide damage in 2004. No association with onset of asthma was observed neither in all students nor in students with previous obstructive airway problems. Among primary school students, there was some suggestion for an association with new use of drugs for obstructive airway diseases, but with highest risk in buildings with limited damage. Conclusions The results from this unique and large follow-up study suggest that assessment of the extent and severity of mold damage inside building structures in Finnish schools do not identify buildings, in which students are at increased risk of developing asthma.